2002
DOI: 10.1677/joe.0.1750779
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the peroxisomal gene expression pattern by dehydroepiandrosterone and vitamin D: therapeutic implications

Abstract: Peroxisomes are ubiquitous organelles required for several metabolic functions. Their dysfunction is responsible for a group of human inherited disorders. In the search for endogenous factors regulating the peroxisomal compartment in normal liver, we treated female rats with dehydroepiandrosterone (DHEA) and 25-hydroxycholecalciferol for 1 and 6 days. Relative transcription levels of 39 selected genes were evaluated by real-time quantitative RT-PCR analysis. Catalase (peroxisomal marker)-specific activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…4), namely, a reduction in the output of aspartate and glutamate, the glutaminase reaction, and the output of ammonia. These changes could be due to metabolism of the PG itself, as it has previously been noted that PG in the perfusate can affect the redox state of the perfused rat liver [54] and that PG in the diet can cause changes in hepatic gene expression [55]. PG (with or without DHEA) injections were carried out under halothane anesthesia; therefore, we cannot exclude an effect of the anesthetic, as it is metabolized by the liver [56].…”
Section: Discussionmentioning
confidence: 99%
“…4), namely, a reduction in the output of aspartate and glutamate, the glutaminase reaction, and the output of ammonia. These changes could be due to metabolism of the PG itself, as it has previously been noted that PG in the perfusate can affect the redox state of the perfused rat liver [54] and that PG in the diet can cause changes in hepatic gene expression [55]. PG (with or without DHEA) injections were carried out under halothane anesthesia; therefore, we cannot exclude an effect of the anesthetic, as it is metabolized by the liver [56].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these steroids reduce AT cellularity (Ryu et al 2003), inhibit preadipocyte differentiation in vitro (Lea-Currie et al 1998), stimulate lipolysis (Tagliaferro et al 1995, Hernández-Morante et al 2008, and alter AT gene expression (Kajita et al 2003, Sánchez et al 2008. In addition, DHEA-S can modulate fatty acid (FA) metabolism, through up-regulation of hepatic enzymes involved in b-oxidation (Waxman 1996, Depreter et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…ALD is a peroxisomal disease and, in animals, DHEAS induces peroxisomal proliferation and the expression of enzymes involved in fatty acid metabolism [12].…”
Section: Discussionmentioning
confidence: 99%